Validation of Garmin HRM-Pro for assessment of spatiotemporal parameters during treadmill running: agreement with three motion analysis systems - Cabrera-Linares, J. C.; Martínez Salazar, C.; Párraga Montilla, J. A.; Latorre Román, P. Á. (Sensors, 2025)
Background: The aim of this study was to validate the accuracy of the spatiotemporal parameters of running provided by the Garmin HRM-Pro band through a concurrent comparison with the OptoGait system (version v.1.14.11), the Stryd power meter, and 2D photogrammetric analysis in recreational runners at different paces (9 and 12 km/h). Methods: Fifty recreational runners (mean age: 22.14 ± 2.71 years) engaged in this study. Participants ran on a treadmill for 2 min at speeds of 9 and 12 km/h. Spatiotemporal parameters (ground contact time, step length, flight time, cadence, and vertical oscillation of center of gravity) were recorded using (1) the Garmin HRM-Pro band; (2) the OptoGait system; (3) the Stryd power meter; and (4) 2D photogrammetric analysis. Results: Only in relation to the VO of the center of gravity does the Garmin device yield higher values (p = 0.006) compared to video analysis. At 12 km/h, significant differences were found between devices in all the analyzed variables. In comparison to video analysis, the Garmin device does not show significant differences in any variable at this speed. The relative reliability parameters of the Garmin device at two different speeds showed excellent values across all analyzed variables. The Bland-Altman plots showed appropriate limits of agreement indicating good agreement between devices. Conclusions: The Garmin HRM-Pro Band can be used for the assessment of spatiotemporal variables of running in sports science, clinical gait assessment, and training optimization.